Uji Aktivitas Ekstrak Karang Lunak Sarcophyton sp Terhadap Staphylococcus aureus - Fatmawati, Andi (Al-Kimia, 2015)
Sarcophyton sp. is one kind of soft corals are today widely studied bioactive content as raw material for making drugs. Some research indicates that extracts Sarcophyton sp. Has many contain terpene compounds that function as antimicrobial, anticancer, antitumor, and anti-inflammantori. Research on Testing Activities Extract Coral Sarcophyton sp against Staphylococcus aureus has been done with the aim to determine the antimicrobial activity of extracts Soft Coral Sarcophyton sp against Staphylococcus aureus. Research conducted by the diffusion method, using iron cylinder diameter in the outer diameter of 6 mm and 8 mm, with an incubation period of 24 hours at 37° C. There are three test concentration of 5%, 10%, and 15% w/v, with the results of each inhibition zone average diameter: 8.91 mm, 9.92 mm and 11.18 mm. In this study a comparison is Tetracycline HCL is used as a positive control with a diameter of inhibition zone produced is 24.18 mm and Na.CMC 1% as a negative control. The results showed that the Soft Coral Sarcophyton sp extract can inhibit the growth of Staphylococcus aureus in consentration 5%, 10%, and 15% w / v. This study found that the higher concentration of the extract Soft Coral Sarcophyton sp has the higher of inhibitory power. The amount of concentration is directly proportional to the diameter of inhibition zone obtained.